(untitled) - Koren, Israel (Amterdam, 2007)
Fault - tolerant systems takes a systems approach to both hardware and software Fault - tolerant, Preliminaries, hardware Fault - tolerance, Information reduundancy....
Keywords: Computer systems,Khắc phục lỗi trong sử dụng máy tính,Fault-tolerant computing; Reliability